2016
DOI: 10.3390/w8010022
|View full text |Cite
|
Sign up to set email alerts
|

Roles of N:P Ratios on Trophic Structures and Ecological Stream Health in Lotic Ecosystems

Abstract: Abstract:Little is known about the functions of N:P ratios in determining trophic structures and ecological health in lotic ecosystems, even though N:P ratios have been frequently used as a stoichiometric determinant in ambient water for trophic allocation of low-level organisms such as phytoplankton or zooplankton. In this study, nutrients (N, P) and sestonic chlorophyll (CHL) from 40 different streams in the Geum-River watershed were measured from 2008 to 2011. Fish compositions and stream health were also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…During summer and winter TN:TP was the better forecaster for CHL than TP, while in spring and autumn TP was a better indicator than TN:TP for the CHL concentrations. This strongly supports the idea that TN:TP ratios determined the primary productivity of the waterbody [33]. According to Jung et al (2016), the primary productivity (CHL-a) of the Korean reservoirs is highly dependent on TN:TP ratios, which is in line with the findings of present study [35].…”
Section: Analysis Of Seasonal Variation Of Primary Productivity On Thsupporting
confidence: 93%
See 2 more Smart Citations
“…During summer and winter TN:TP was the better forecaster for CHL than TP, while in spring and autumn TP was a better indicator than TN:TP for the CHL concentrations. This strongly supports the idea that TN:TP ratios determined the primary productivity of the waterbody [33]. According to Jung et al (2016), the primary productivity (CHL-a) of the Korean reservoirs is highly dependent on TN:TP ratios, which is in line with the findings of present study [35].…”
Section: Analysis Of Seasonal Variation Of Primary Productivity On Thsupporting
confidence: 93%
“…Quality Parameters TN:TP ratio is a good surrogate variable of ambient nutrient concentrations of the Korean watershed [33]. The TN:TP was highly influenced by water temperature (WT, ºC), biological oxygen demand (BOD, mgL -1 ), chemical oxygen demand (COD, mgL -1 ), dissolved oxygen (DO, mgL -1 ), hydrogen ion concentration (pH), and total suspended solids (TSS, mgL -1 ; Fig.…”
Section: Analysis Of Tn:tp Ratios With Other Watermentioning
confidence: 99%
See 1 more Smart Citation
“…One of them concerns nutrients and their concentration that are essential in the determination of phytoplankton composition and abundance in aquatic systems (Abate et al 2017). NO 3 and PO 4 are among the most important of these nutrients and their ratio (N:P) may be used as an efficient tool for determining of the trophic state of water bodies (Yun and An 2016).…”
Section: Phytoplankton As a Bio-indicatormentioning
confidence: 99%
“…Yun and An [22] assessed the influence of land use patterns on nutrient contents and N:P ratios in stream ecosystems, and determined the empirical relationships between N:P ratios and nutrients and sestonic algal biomass. Their results indicated that land use patterns in the study watersheds are a key factor regulating nutrient contents and N:P ratios in ambient water, and influenced empirical relationships between N:P ratios and sestonic chlorophyll.…”
Section: Contributionsmentioning
confidence: 99%